THE URGENCY OF JURISPRUDENCE IN ACTUALIZATION ISLAMIC LAW - Juswandi; Jumni Nelli; Erman Gani (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
Human life that continues to develop in accordance with its human nature, makes many new cases appear without any legal provisions in both the Quran and hadith. The evolving dynamics of society are not in line with the static legal text. Based on these conditions, it is necessary to re-actualize Islamic law. Another problem that comes to the fore is that to re-actualize there must still be a mechanism or formula in finding the new law. The rules of jurisprudence apparently provide concrete solutions to the need for a method or method of finding the law (istinbath al-ahkam). With the rules of jurisprudence, it is hoped that contemporary problems can be found as an application to the reactualization of Islamic law.